2021
DOI: 10.1002/jemt.23981
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological evaluation of Daphne mucronata Royle and Myrtus communis L. using scanning electron microscopic techniques

Abstract: The present study was undertaken to establish micromorphological standards of Daphne mucronata Royle and Myrtus communis (L.). Daphne mucronata Royle is a xerophytic perennial shrub while, Myrtus communis is an evergreen shrub or small tree. Micromorphological investigation is one of the cheapest methods. It will be helpful in the accurate identification of these plants from other species. Results of macroscopic evaluation showed various organoleptic features. Anatomy of the selected plant parts was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For stomatal study, leaves were washed carefully under running water to get rid off dirt, debris and let them to dry. The upper and lower epidermis of leaves were peeled off wisely until a thin membrane with sharp razors taken from the Madina market, University of Peshawar, followed Dastagir et al (2022). A cover slip was placed over it after spreading one or two drops of water/glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…For stomatal study, leaves were washed carefully under running water to get rid off dirt, debris and let them to dry. The upper and lower epidermis of leaves were peeled off wisely until a thin membrane with sharp razors taken from the Madina market, University of Peshawar, followed Dastagir et al (2022). A cover slip was placed over it after spreading one or two drops of water/glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative and quantitative microscopic characters have been reported to be vital in plant identification and drug evaluation in Pharmacognosy, especially when they are in fragmented form. 2 Specifically, Gul et al 43 reported the use of quantitative parameters like dimension of trichomes, epidermal cells and stomatal index which were successfully utilized in delimiting 22 Lamiaceae species from 15 genera. The present investigation conforms to Gul et al 43 assertion that quantitative measurements like epidermal cell size, glandular trichome size, and non-glandular trichome size served as an important tool in distinguishing the three wild Dioscorea species and indeed can also aid recognition of cultivars of D. bulbifera and D. dumetorum.…”
Section: Quantitative Description Of Epidermal Featuresmentioning
confidence: 99%